From marginality to legitimate peripherality: understanding the essential functions of a women's program - (:unkn) unknown (JOHN WILEY & SONS INC, 2008)
The focus of this research was to understand how a program for women in science, mathematics, and engineering (SM&E) at college level in the southeastern United States functioned to influence women's decision making in terms of participation in these fields. By employing Lave and Wenger's theory of situated learning, we explored this program through two and a half academic years. We utilized a qualitative-quantitative mixed approach in our methodology. For the case study aspect, we focused on the cases of three women participating in the support program via participant observations and in-depth interviews. For a more general description, we developed a questionnaire and augmented this with interviews with a broad spectrum of students. Our findings illustrated that the program demonstrated a great potential to aid the traditionally marginalized to move from marginality to legitimate participation in the communities of science. The program functioned successfully in four ways, each interwoven with the others. One implication of these findings is that such programs should include a multitude of events and opportunities for cognitive, social, and emotional support. Being not tall orders financially, such programs may be considered as effective interventions in both national and international settings, where women are in disadvantaged status. (c) 2007 Wiley Periodicals, Inc.
Keywords: SCIENCE; SCIENTISTS; EDUCATION; FEMINISM